PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL, PERTUMBUHAN PENJUALAN, DAN PERPUTARAN ASET TERHADAP NET PROFIT MARGIN PADA PERUSAHAAN SEKTOR TEKNOLOGI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Indah Leony Panjaitan; Bella Ariboho Sihaloho; Arie Pratania Putri; Rahima Br Purba (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze and examine the effect of company size, capital structure, sales growth, and asset turnover on net profit margin in technology sector companies listed on the Indonesia Stock Exchange for the 2022-2024 period. The population studied included all 46 technology sector companies listed on the IDX. The sampling technique used was purposive sampling, resulting in 15 companies as samples. The data analysis method used was multiple linear regression analysis. The results showed that capital structure and asset turnover partially influenced net profit margin. Meanwhile, company size and sales growth did not. The results showed that company size, capital structure, sales growth, and asset turnover simultaneously influenced net profit margin. The coefficient of determination analysis showed that the combination of company size, capital structure, sales growth, and asset turnover explained 20.4% of the variation in net profit margin, while the remaining 79.6% was influenced by other variables.